The Contribution Of Marine Tourism To Msme Income, Community Welfare, And Tourists Revisit Intention In Pahawang Island - Candani Rahmah; Neli Aida (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Marine tourism development has become one of the important sectors in promoting the economic growth of coastal communities through increased business activities and local economic opportunities. Pulau Pahawang, as a leading marine tourism destination in Pesawaran Regency, has significant potential to support the development of local Micro, Small, and Medium Enterprises (MSMEs) while maintaining the sustainability of tourist visits. This study aims to analyze the contribution of marine tourism to the income and welfare of local MSMEs, as well as the influence of tourist perceptions on revisit intention in Pulau Pahawang. The study employed economic contribution analysis, the Sajogyo Poverty Index, and Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that marine tourism in Pulau Pahawang contributes 100% of income for the majority of local MSMEs, and all MSME actors are classified as prosperous based on the Sajogyo Poverty Index classification. In addition, tourist attraction, facilities and accessibility, as well as service and interaction were found to have a positive and significant effect on tourists’ revisit intention. These findings indicate that the sustainability of marine tourism not only contributes to the economic activities of local MSMEs, but is also influenced by tourists’ perceptions of destination quality.